Exploring the Interaction between Local Communities and Environmental Policies: A Qualitative Study of Conflicts between Natives and Rangers around the Protected Areas of Bojaq National Park - Yaser Khoshsirat Salimi; Ali Ruhani; Hossein Afrasiabi; Sadegh Salehi (جامعه شناسی کاربردی)
Introduction Easy access to resources in natural areas serves as a motivating factor for the continued use of these resources by local communities, often leading to resistance against the protection of natural assets. Conversely, the government and environmental organizations, in pursuit of sustainable development for the benefit of current and future generations, are working to regulate exploitation by hunters. Reports from both official and unofficial sources, as well as observations in Iran, indicate a conflict between park wardens and local communities in and around protected areas. To understand this challenge, a review of the relevant literature was conducted. The research aimed to develop theoretical sensitivity by focusing on specific concepts through existing research and theories, which informed the entry into the research field and the design of the interview protocol. The study focused on the communities surrounding Bojaq National Park located in Bandar Kiasher (Gilan Province). Sampling was conducted and the primary data collection method was in-depth interviews. The interview protocol included questions about the causes of resistance among local hunters and their lifestyle, as well as mechanisms of conflict and adaptation. It also explored the advantages and disadvantages of their way of life in relation to the environmental and fisheries organizations, as well as significant social structures. Additionally, the reasons for their cultural solidarity were examined. This approach aimed to understand the underlying factors contributing to the escalating resistance between them and government agents from the locals’ perspective. The interview protocol was designed to address these sensitive concepts comprehensively.